Efeito cito-genômico do peróxido de hidrogênio e do guaraná (Paullinia cupana) em células tronco mesenquimais - Machado, Alencar Kolinski (2014)
With advances in techniques of cell culture, stem cells (SCs) have to be used as an alternative therapy, firming the called regenerative medicine. An type of SC that has been studied is the Adipose-derived stem cell (ASCs) having identical characteristics of Mesenchymal Stem Cells (MSCs). To realize a transplanting of SCs, is necessary a large amount of cells, which makes such cultures are maintained in vitro for long periods of time, consequently these cells, with the repeated passages, enter cellular senescence, which prevents their use. Thus, some studies showed that the hydrogen peroxide (H2O2) can act to potentiate the proliferation of these cells. However, it is know that the oxidative metabolism can be associated with the senescence process. From this, the aim of this study was available the cito-genomic effect of the exposition of ASCs to H2O2 and to guaraná extract. Was realized isolation and cultivation of ASCs, that were, in forth passage, exposed to concentrations of 1-1000 μM of H2O2 and realized assays to available the cell viability, oxidative stress parameters, DNA damage and the apoptotic way of caspases. Moreover, senecents ASCs were treated with concentrations of 1-20 mg/mL of guaraná extract, being tested to the senescence reversion, cell viability, oxidative parameters, DNA damage and activity and expression of antioxidants enzymes. The results showed that the H2O2 cause cito-genomic damages to ASCs, with decrease in the cell viability mainly at the concentration of 200 μM, as well as increase the total reactive oxygen species (ROS) rate and lipidic peroxidation effect. The H2O2 also decreased the catalase activity in dose-dependent form e acted in the SOD activity. The treatments also conducted to a progressive increase of DNA damage. Moreover, in the eighth passage was observed the senescence of ASCs and the treatment with guaraná showed capacity to revert this phenotype in the concentration of 5 mg/mL, with reduction in the total ROS rate, lipoperoxidation, protein carbonyl and DNA damage, when compared with senescent ASCs untreated. The guaraná also was able to modulate the activity and expression of antioxidants enzymes, increasing the catalase, decreasing the total SOD and a light decrease in the glutathione peroxidase was observed. Therefore, it can be said that the acute exposition of no senescent ASCs to H2O2 was highly cytotoxic, demonstrating the high sensibility of these cells to this stressor agent. However, senescent ASCs treated with guaraná showed the potential effect of this extract in the reversion of the cellular senescence.